2009
DOI: 10.1007/s10508-009-9512-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex Typicality and Attractiveness in Childhood and Adulthood: Assessing their Relationships from Videos

Abstract: Prior research suggests that sex typicality (especially femininity of females, but also masculinity of males) relates to perceptions of attractiveness, for both heterosexual and homosexual individuals. Using videos from childhood and adulthood, we investigated how different components of sex typicality contributed to this effect, whether the sex of the evaluator or of the target moderated the effect, and how the relationship of attractiveness with sex typicality varied across the lifespan. In Study 1, videos o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…Second, participants in the present study did not rate the victim and defendant images for attractiveness. Research has shown that gender typicality (i.e., femininity for women) affects perceptions of attractiveness (Rieger et al, 2011), and mock jurors generally perceive attractive defendants as less guilty than plain-looking defendants (Mazzella & Feingold, 1994). However, the pattern of trial rating results in the present study does not seem to be explainable as an attractiveness effect.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Second, participants in the present study did not rate the victim and defendant images for attractiveness. Research has shown that gender typicality (i.e., femininity for women) affects perceptions of attractiveness (Rieger et al, 2011), and mock jurors generally perceive attractive defendants as less guilty than plain-looking defendants (Mazzella & Feingold, 1994). However, the pattern of trial rating results in the present study does not seem to be explainable as an attractiveness effect.…”
Section: Discussioncontrasting
confidence: 87%
“…However, the pattern of trial rating results in the present study does not seem to be explainable as an attractiveness effect. For instance, men's ratings of attractiveness of women are strongly influenced by gender typicality (Rieger et al, 2011), yet male participants had more sympathy for a masculine victim. Future studies should measure and covary attractiveness, so it is not confounded with masculinity or femininity.…”
Section: Discussionmentioning
confidence: 99%
“…These men and women were originally interviewed at a Midwestern university in the USA. In total there were 185 non-explicit sexual stimuli whose attractiveness has been previously assessed (Rieger et al, 2011), and the most attractive men and women were used in the present study. The average age (SD) was 21.67 (1.72) years and 22.83 (3.83) years, respectively.…”
Section: !mentioning
confidence: 99%
“…If attractive women are seen as more feminine (Heilman & Saruwatari, 1979;Drogosz & Levy, 1995;Rieger et al, 2009), and femininity is antithetical to the masculinized ideal worker norm (Acker, 1990), attractive women may be disadvantaged in the paid labor market relative to unattractive women who are seen as less feminine. In a classic study, Heilman and Saruwatari (1979) find that sometimes "beauty is beastly" − attractiveness helped women in non-managerial positions, but actually hurt women who were managers.…”
Section: Introductionmentioning
confidence: 99%